(untitled) (Al-Mansour Journal, 2023)
The International commercial arbitration is one of the vital mean to settle the disputes arising from the international commerce, either because there are not international courts specified to deal with the international commercial transactions, or the desire of the concerned parties of the international commercial disputes to avoid subjecting their disputes to the jurisdiction of specific country. It is worth to mention that the international commercial arbitration stirs many legal problems worldwide either connected to defining the international nature of arbitration, or determining the law which should be applicable either on the procedural or substantive level. The researcher identified the most important legal problems arising from the international commercial arbitration and tried to propose the appropriate legal solution according to scientific plan divided into chapters concluded by some results and recommendations.